Centring The Periphery: Local Identity in the Music of Theodore Antoniou and other Twentieth-Century Greek Composers - Andronikou, Michalis; Sallis, Friedemann (Intersections)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2012)
This study addresses aspects of local identity in the music of Theodore Antoniou and other Greek contemporary composers. It highlights misapprehensions and obsolete conceptions of historiography and aesthetics embedded in the use of terms such as centre and periphery or high- and low-brow styles of music, respectively. An overview of the history of art music in Greece is attempted, for a better understanding of these issues in that context. The parallel reference to significant Western contemporary composers such as György Ligeti, Luigi Nono, and Mauricio Kagel supports the primary argument of the essay, which seeks fair treatment for all places that find themselves peripheral to a given centre. The case of Greece—one of the cradles of Western culture—is a unique example of a problematic approach typical of Western historiographies with regard “centres” and “peripheries” that needs to be corrected.